Sustainable rural development : sustainable livelihoods and the community capitals framework - Emery, Mary; Gutierrez, Isabel; Fernandez-Baca, Edith (London: Routledge, 2013)
This text brings together several systems-level approachesto the consideration of the interaction of livelihood choices, natural resource management and participatory action research on sustainable development. By focusing on these approaches to community change, the volume hopes to encourage readers to consider how they might adopt methods such as Sustainable Livelihoods Approach (SLA), Community Capitals Framework (CCF) and Participatory Action Research (PAR) in their own research, practice and teaching